PENGARUH UPAH DAN FASILITAS TERHADAP PRODUKTIVITAS MARKETING KREDIT PADA PT BANK RAKYAT INDONESIA.Tbk DI KABUPATE MIMIKA - Siske Tontong (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2021)
This study aims to analyze the effect of wages and facilities on credit marketing productivity at PT Bank Rakyat Indonesia Tbk. in Mimika Regency. The research method used in this research is the associative method. Data collection techniques were carried out by observation, questionnaires/questionnaires, documentation, and literature studies. The analytical instrument used is the Chi Square K sample analysis. The results showed that there was an influence of facilities on credit marketing productivity at PT Bank Rakyat Indonesia Tbk. in Mimika Regency while wages have no effect on credit marketing productivity of PT Bank Rakyat Indonesia Tbk. in Mimika Regency.